Aspects regarding the regulation of liability in the Administrative Code - Ghencea, Flavia Lucia (Technium Social Sciences Journal, 2021)
A fundamental act for the Romanian administration was adopted in July 2019, namely the Administrative Code, which came into the legal landscape with the declared intention of contributing to the modernization of public administration, systematizing the legislation in the field and bringing more unity to the organization of law enforcement and to its concrete execution. The text transposes in a clear and unitary form, a series of already existing regulations, in separate normative acts, but also adds new legal institutions that contribute to increasing the coherence of the administrative activity. This paper aims, on the one hand, at analyzing an institution that comes as a novelty in the Romanian regulatory framework, the administrative liability, as form of liability specific to administrative law and, on the other hand, it is a brief analysis of a form of liability missing from the text of the Code, namely the ministerial liability.